New Insights Into the Plastome Evolution of the Millettioid/Phaseoloid Clade (Papilionoideae, Leguminosae) - Oyebanji, Oyetola; Zhang, Rong; Chen, Si-Yun; Yi, Ting-Shuang (Frontiers in Plant Science, 2020)
The Millettioid/Phaseoloid (MP) clade from the subfamily Papilionoideae (Leguminosae) consists of six tribes and ca. 3,000 species. Previous studies have revealed some plastome structural variations (PSVs) within this clade. However, many deep evolutionary relationships within the clade remain unresolved. Due to limited taxon sampling and few genetic markers in previous studies, our understanding of the evolutionary history of this clade is limited. To address this issue, we sampled 43 plastomes (35 newly sequenced) representing all the six tribes of the MP clade to examine genomic structural variations and phylogenetic relationships. Plastomes of the species from the MP clade were typically quadripartite (size ranged from 140,029 – 160,040 bp) and contained 109 –111 unique genes. We revealed four independent gene losses (ndhF, psbI, rps16, and trnS-GCU), multiple IR-SC boundary shifts, and six new inversions in the tribes Desmodieae, Millettieae and Phaseoleae. Plastomes of the species from the MP clade have experienced significant variations which provide valuable information on the evolution of the clade. Plastid phylogenomic analyses using Maximum Likelihood and Bayesian methods yielded a well-resolved phylogeny at the tribal and generic levels within the MP clade. This result indicates that plastome data is useful and reliable data for resolving the evolutionary relationships of the MP clade. This study provides new insights into the phylogenetic relationships and PSVs within this clade.